Intersectoral Experiences: Nonprofit Managers and Sector Influences in Child Welfare Agencies. Issue 1 (1st January 2017) - Robichau, Robbie Waters; Fernandez, Kandyce
ABSTRACT: Theory supports the notion that the societal sectors are blurring and blending and therefore questions the usefulness of employing the sectors as a theoretical construct. This paper grapples with this critique of the sectors as theoretically beneficial by using nonprofit, child-welfare administrators' perspectives on how normative institutions and values espoused by and through government, for-profit, and nonprofit organizations inform decision-making priorities. Through examining data from approximately 147 managers, this paper will show how administrators identify with and may be compelled to conform to pressures that result from their relation to government, for-profit, and other nonprofit organizations.